Primary structure of streptococcal Pep M5 protein: Absence of extensive sequence repeats - Manjula, Belur N. (1983)
Extensive sequence repeats have been observed in a biologically active fragment of type 24 streptococcal M protein, namely Pep M24 [Beachey, E. H., Sayer, J. M. & Kang, A. H. (1978) Proc. Natl. Acad. Sci. USA 75, 3163-3167]. To determine whether such extensive repetition in sequence is a common characteristic of the antiphagocytic streptococcal M proteins, we have determined the sequences of the clostripain peptides of Pep M5, a biologically active fragment of the type 5 M protein that is analogous to Pep M24. These sequences, together with the amino-terminal sequence of the whole molecule, accounted for nearly two thirds of the Pep M5 molecule. However, extensive identical repeats of the kind observed in Pep M24 were not present in Pep M5. Preliminary study of the amino acid sequence analysis of the M protein from type 6 Streptococcus has also indicated the absence of sequence repeats within the regions of this molecule examined so far. These results suggest that extensive sequence repeats may not be a common characteristic of M-protein molecules. On the other hand, the seven-residue periodicity of the nonpolar residues, a characteristic of α-helical coiled-coil structures, appeared to extend over most of the Pep M5 molecule. This feature has been observed previously for the partial sequences of three M protein serotypes. Thus, the important element of the M-protein structure appears to be the seven-residue periodicity necessary for the maintenance of the coiled-coil structure rather than extensive identical amino acid sequence repeats.